Asymmetrically CPW-fed ladder-shaped fractal antenna for UWB applications - Singhal S.; Singh A.K. (My University, 2025)
A compact asymmetrically CPW-fed ladder- shaped UWB fractal antenna is presented. An impedance bandwidth of 4.56–13.1 GHz is achieved by using four iterations of H-shaped radiating element, modified feed line, asymmetrical feeding and slot loaded ground plane. Omnidirectional radiation patterns are achieved in H-plane at all frequency points in the operating frequency band. The bidirectional nature of E-plane patterns at lower frequencies is observed to be shifted to directional nature at higher frequencies. The designed antenna structure has an average gain of 2.84 dB with a constant group delay. The designed antenna structure is analyzed for three different substrate materials i.e. CNT, Ni0.2Co0.2Zn0.6Fe2O4 and FR-4 epoxy. A good agreement is achieved between the simulated and measured results. This antenna structure has advantages of wider bandwidth and smaller dimensions over already reported ones. © 2017, Springer Science+Business Media New York.